Schizophrenia Associated with Epileptiform Discharges without Seizures Successfully Treated with Levetiracetam - Endres, Dominique; Perlov, Evgeniy; Feige, Bernd; Altenmüller, Dirk-Matthias; Venhoff, Nils; Tebartz van Elst, Ludger (Frontiers in Psychiatry, 2017)
Background: Schizophrenia-like disorders can be divided into endogenic or primary, idiopathic, polygenetic forms, and different secondary, organic subgroups (e.g., [para]epileptic, immunological, degenerative). Epileptic and paraepileptic explanatory approaches have a long tradition due to the high rate of electroencephalography (EEG) alterations in patients with schizophrenia. Case presentation: We present the case of a 23-year-old female patient suffering, since the age of 14 years, from a fluctuating paranoid-hallucinatory syndrome with formal thought disorder, fear, delusions of persecution, auditory, visual, and tactile hallucinations, as well as negative and cognitive symptoms. Laboratory measurements showed increased titers of antinuclear antibodies (ANAs) in the context of ulcerative colitis. While there was no clear history or evidence of epileptic seizures, the EEG showed generalized 3 Hz polyspike wave complexes. Under treatment with levetiracetam, the symptoms disappeared and the patient was able to complete vocational training. Conclusion: The schizophrenia-like symptoms associated with epileptiform discharges but not overt seizures and the good response to antiepileptic treatment could be interpreted in the context of a (para)epileptic pathomechanism. The EEG alterations might be due to a polygenetic effect due to different genes. Mild immunological mechanisms in the framework of ulcerative colitis and increased ANA titers might have supported the network instability. This case report illustrates 1) the importance of EEG screenings in schizophrenia, 2) a potential pathogenetic role of epileptiform discharges in a subgroup of patients with schizophrenia-like symptoms, and 3) that antiepileptic medication with levetiracetam could be a successful treatment alternative in schizophrenia-like disorders with EEG alterations.